Nurses' perception regarding barriers to use of health information system in the teaching hospital of Abbottabad: Nurses' perception regarding barriers to use of health information system - Khan, Sheraz; Sultan, Amir; Hanif, Javaria; Jamil, Kinza; Batool, Zara (Pakistan Journal of Health Sciences, 2022)
The Health Management Information System (HMIS) was designed to provide information on the status of ongoing health-related events. It has been designed to enhance data management in health care facilities. The effectiveness of this system depends on the appropriate collection, analysis, interpretation, and utilization of data. Objective: This study intended to generate knowledge to bridge this knowledge gap to overcome barriers to using and implementing integrated HIS. Methods: Descriptive cross-sectional design was used in this study. The data were collected in a Teaching hospital in Abbottabad from July 27, to Aug 3, 2022. Five item Likert scale was used to collect data from 206 nurses. Those who have one-year of experience with HMIS were included in this study. Result: More than half 51.9 % (n=107) of the study participants were female. Almost half 49.5% (n=102) of the participants responded with little and very few barriers in the use of health information systems, followed by much and very much by one-fourth of the participants 25.7% (n=53) and moderate 24.8% (n=51). technical (2.98±1.17) had the highest total mean scores followed by legal (2.95±1.19), organizational (2.91±1.15), and personal (2.90±1.16). Conclusions: The study concluded technical barrier as the top most and comprises computer shortage, internet breakdown and improper health information network. The nurses also reported workload due to documentation and access of an unauthorized person to information